From cellular memory to the memory of trauma: Social epigenetics and its public circulation. (March 2020) - Dubois, Michel; Guaspare, Catherine
Trauma is associated with the appearance of the concept of 'accident' as a social and legal entity, as well as with the successive discoveries of surgery, psychiatrics, and psychoanalysis. Today, epigenetics has redefined trauma as an extreme form of social adversity. Because of the exceptional nature of the events studied and also the social and political significance of its results, the social epigenetics of historical trauma has received undeniable public success. The present article investigates the general dynamics of this research front, as well as the forms and consequences of its public circulation. We highlight the specificity of the circulation modes associated with social epigenetics and the myriad ways it has been used socially and politically. This study addresses four registers of action in particular: to attest, to repair, to intervene, and to treat. The social circulation of the epigenetics of trauma is as influenced by the public's willingness to see it as socially and politically relevant as it is by the ability of researchers to prepare this collective appropriation through different forms of public engagement. Finally this study allows us to refute the dichotomic conception of the genetics/epigenetics relationship, which is too frequently the foundation for making epigenetics academically acceptable in the social sciences.